(untitled) (Fiep Bulletin - online, 2014)
The work presents the results of a research on the impact of the programme of exercises on the development of selected coordination abilities and the speed of acquisition of cartwheel in 10–11-year-old pupils. The object of the research were 34 pupils from the 8-year secondary grammar school in Nitra. Coordination abilities were developed during the period of 5 months and then, the acquisition of cartwheel was implemented. Each pupil should realize 15 attempts, which were assessed by the panel of three independent evaluators – teachers using the marks between 1 and 5. The following results were calculated based on average values: The speed of acquisition was showed more strikingly in the experimental group, as a consequence of the special coordination training. When assessing the quality of cartwheel performance we came out of the statements by Melicher & Slezák (2004), who consider the standard to be fulfilled, when 75% of pupils from the observed group fulfilled the criterion. We also followed the opinions of Antala (1997), who presents that the mark 2 (praiseworthy) corresponds to the technically independently acquired gymnastic element with a sporadic occurrence of medium errors of aesthetic character. By the combination of these criteria and based on the results of the work it was proved that the speed of motor learning was higher in the experimental group. The speed of acquisition was influenced mainly by the changes in the level of dynamic balance and to a limited level also in the level of static balance and kinesthetic-differentiation ability of legs. Rhythmic and spatial orientation abilities showed only a small share on the final performance.